ChemInform Abstract: Model Studies on Heterogeneous Catalysts at the Atomic Scale: From Supported Metal Particles to Two‐dimensional Zeolites. Issue 6 (11th February 2014) - Freund, Hans‐Joachim; Heyde, Markus; Nilius, Niklas; Schauermann, Swetlana; Shaikhutdinov, Shamil; Sterrer, Martin
Abstract Review: 108 refs.